Bromine-functionalized porous coordination polymer, preparation method and application in natural gas purification

By preparing bromine-functionalized porous coordination polymer (PCP-Br), the problems of CO2 removal and C2H6/C3H8 separation in natural gas are solved, and efficient and selective natural gas adsorption and purification effects are achieved.

CN118955936BActive Publication Date: 2025-01-21DEZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411419311.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-21
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove CO2 in natural gas, and it is difficult to efficiently separate C2H6 and C3H8, affecting the combustion efficiency of natural gas and the safety of pipeline transportation.

Method used

A dual-ligand strategy was used to prepare bromine-functionalized porous coordination polymer (PCP-Br) through solvothermal synthesis. Its chemical formula is [Ni3(OH)(TMBTTP)(BDC-Br)3] and it has cage-like porous structure and high specific surface area.

Benefits of technology

PCP-Br material shows high CO2 adsorption efficiency, selectivity and low energy consumption in natural gas adsorption and purification applications. It can effectively separate CH4, CO2, C2H6 and C3H8, and improve the quality and production efficiency of natural gas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118955936B_ABST
    Figure CN118955936B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of crystal materials and natural gas purification, and in particular to a bromine-functionalized porous coordination polymer, a preparation method and a natural gas purification application. The chemical formula of the porous coordination polymer is [Ni3(OH)(TMBTTP)(BDC‑Br)3]. The crystal material structure of the polymer is novel and the framework is stable. There are two types of cages: cylindrical and spindle-shaped. The specific surface area is 822.7 m 2 g −1 The pore size distribution is 6.2-6.8 Å. The permanent pores, suitable pore size and bromine-modified pore environment make the porous coordination polymer suitable for natural gas purification.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of crystal materials and natural gas purification, and in particular to a bromine-functionalized porous coordination polymer, a preparation method and application of natural gas purification. Background Art

[0002] As an energy source, natural gas has relatively low carbon emissions and is considered a clean alternative to traditional fossil fuels such as gasoline and diesel. The main component of natural gas is methane (CH4), but it also contains other components, including hydrocarbons such as carbon dioxide (CO2), ethane (C2H6) and propane (C3H8). However, the presence of CO2 in natural gas can reduce its combustion efficiency and even cause pipeline corrosion during transportation. Therefore, removing CO2 from natural gas is crucial to improving the quality of natural gas and ensuring the safety of pipeline transportation. In addition, separating and recovering C2H6 and C3H8 from natural gas is conducive to improving the conversion rate of CH4, maximizing the utilization of C2H6 and C3H8, and improving production efficiency. Among them, adsorption technology is an important solution for removing CO2 due to its advantages such as mild operating conditions and low energy loss. Its core technology is the development of advanced adsorption materials. Therefore, in order to further provide materials with high CO2 adsorption efficiency, high selectivity and low energy consumption, people have been working hard to find and develop new porous adsorbent materials.

[0003] Porous coordination polymers (PCP) are crystalline porous materials formed by self-assembly of metal ions / clusters and organic ligands. Due to their customizable structure, adjustable pore properties and high specific surface area, PCP materials have shown excellent performance in gas adsorption and separation, and have attracted widespread attention and favor from researchers and the market. The pore surface of PCP materials can be designed with molecular / atomic functional sites to achieve accurate recognition of adsorbate molecules to improve the selectivity and binding force of the adsorption process. In addition, PCP materials have extremely high specific surface area and can provide a large adsorption surface. In view of the above-mentioned characteristic advantages of PCP materials, the present invention adopts a dual ligand strategy and uses a solvent thermal synthesis method to prepare a PCP with a cage-like porous structure. The selected dicarboxylic acid ligand is modified with bromine (Br) atoms, so that the porous cavities of the prepared PCP are functionalized with Br. The structure, porous properties and application performance of the material in natural gas adsorption purification are confirmed by characterization and testing methods such as single crystal X-ray diffraction, gas adsorption, and mixed gas fixed bed separation. The material involved in the invention has the basic characteristics of being an adsorbent for natural gas purification and has the potential for commercial development. Summary of the invention

[0004] One of the purposes of the present invention is to provide a bromine-functionalized porous coordination polymer, wherein the chemical formula of the bromine-functionalized porous coordination polymer is [Ni3(OH)(TMBTTP)(BDC-Br)3], wherein one of the ligands used is 4,4',4'-(2,4,6-trimethylbenzene-1,3,5-triphenyl)tripyridine TMBTTP, and the second ligand is H2BDC-Br is 2-bromoterephthalic acid, named PCP-Br;

[0005] Furthermore, the crystal structure of the PCP-Br belongs to the trigonal system, and the space group is P- 31c, the unit cell parameters are: a =16.943(3) Å, b =16.943(3) Å, c=15.034(6) Å, α = β = 90 o , γ = 120 o .

[0006] Furthermore, in the three-dimensional framework structure of PCP-Br, its crystallographic asymmetric structural unit includes 1 Ni(II) ion, 1 / 3 -OH group, 1 H2BDC-Br ligand and 1 / 3 TMBTTP ligand;

[0007] The Ni(II) ion is coordinated with six atoms in an octahedral configuration, including four O atoms of carboxyl groups from different H2BDC-Br ligands, one O atom of the -OH group, and one N atom from the TMBTTP ligand;

[0008] Three adjacent Ni(II) ions are bridged by one -OH group and six carboxyl groups of six different H2BDC-Br ligands to form a typical trinuclear metal cluster [Ni3(μ3-OH)(COO)6];

[0009] Each metal cluster is alternately connected with H2BDC-Br ligands to form a three-dimensional porous structure with acs topological configuration; TMBTTP ligands connect [Ni3(μ3-OH)(COO)6] clusters, further dividing them into a three-dimensional framework with pacs topological structure.

[0010] Furthermore, in the PCP-Br structure, there are cylindrical cages A and spindle-shaped cages B, wherein the upper and lower planes of the cylindrical cage A contain three [Ni3(μ3-OH)(COO)6] clusters and one TMBTTP ligand, respectively, and the wall of the cylinder is occupied by six H2BDC-Br, and the bottom diameter and height of the cylindrical cage A are 7.9 and 2.7 Å, respectively;

[0011] The upper and lower vertices of the spindle-shaped cage B are respectively occupied by one [Ni3(μ3-OH)(COO)6] cluster, and three [Ni3(μ3-OH)(COO)6] clusters are evenly distributed in the middle part. The vertices and the middle clusters are connected by H2BDC-Br ligands, and the three middle [Ni3(μ3-OH)(COO)6] clusters are connected by TMBTTP ligands. The distance between the vertices of the spindle-shaped cage is 8.2 Å, and the diameter at the middle position is 8.1 Å.

[0012] The present invention also provides a method for preparing the bromine-functionalized porous coordination polymer, comprising the following steps:

[0013] Under sealed conditions, organic ligands 4,4',4'-(2,4,6-trimethylbenzene-1,3,5-triphenyl)tripyridine (TMBTTP), 2-bromoterephthalic acid (H2BDC-Br) and nickel nitrate hexahydrate (Ni(NO3)2·6H2O) were dissolved in N , N - A mixed solution of dimethylacetamide and water, and a proper amount of acid is added to adjust the acidity of the solution, a sample is obtained through a solvent thermal reaction, and then the sample is activated to obtain a PCP-Br porous coordination polymer crystal material.

[0014] Furthermore, the temperature of the solvent thermal reaction is 90-120° C., and the reaction time is 18-48 hours.

[0015] Further, the molar ratio of the organic ligand TMBTTP, H2BDC-Br and Ni(NO3)2·6H2O is 1:(3~5):(3~5);

[0016] Every 0.1 mmol of TMBTTP corresponds to 10-12.5 mL of DMA;

[0017] The volume ratio of DMA to water is 1:(0.1~0.4);

[0018] Each 1 mL of DMA corresponds to 10~30 μL of 52 wt% tetrafluoroboric acid aqueous solution.

[0019] Furthermore, the activation method of the bromine-functionalized porous coordination polymer sample comprises the following steps: first, washing the synthesized sample three times with ethanol, soaking the washed sample in an ethanol solution for 48 hours, stirring continuously and replacing ethanol 6 times, filtering, and then drying in a vacuum oven at 100°C for 5 hours to obtain an activated sample.

[0020] The third object of the present invention is to provide the use of the bromine-functionalized porous coordination polymer in the purification of natural gas.

[0021] Beneficial technical effects of the present invention: The bromine-containing porous coordination polymer crystal material of the present invention has a novel structure and a stable framework, and has two types of cages: cylindrical and spindle-shaped. The specific surface area of ​​the bromine-based porous coordination polymer material PCP-Br is 822.7 m 2 g −1 The pore size distribution of PCP-Br is 6.2-6.8 Å. The permanent pores, suitable pore size and bromine-modified pore environment make this porous coordination polymer suitable for natural gas purification. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a single crystal photo of PCP-Br under a microscope;

[0023] Figure 2 This is a photo of a powdered crystal sample of PCP-Br;

[0024] Figure 3 The structural diagram of the Ni metal center in PCP-Br;

[0025] Figure 4 The three-dimensional framework structure of PCP-Br

[0026] Figure 5 The structural diagram of the cylindrical cage A and the spindle-shaped cage B in PCP-Br;

[0027] Figure 6 The powder X-ray diffraction spectra of synthesized PCP-Br and its treatment under different conditions;

[0028] Figure 7 is the thermogravimetric curve of PCP-Br;

[0029] Figure 8 is the infrared spectrum of PCP-Br;

[0030] Fig. 9 The 77 K nitrogen adsorption isotherm and pore size distribution of PCP-Br;

[0031] Fig.10 The single component adsorption isotherms of CH4 and other components (CO2, C2H6, C3H8) on PCP-Br at 298 K and 313 K and 100 kPa;

[0032] Fig.11 It is the adsorption heat curve of PCP-Br to CH4 and other components (CO2, C2H6, C3H8);

[0033] Fig.12Schematic diagram of the equimolar dynamic breakthrough curves of PCP-Br for CH4 and other components (CO2, C2H6, C3H8) at 298 K;

[0034] Fig.13 Cycle diagram for the dynamic gas adsorption separation test of PCP-Br. DETAILED DESCRIPTION

[0035] The present invention will be further described below in conjunction with examples, but the present invention is not limited to the following examples.

[0036] Example 1

[0037] The organic ligands TMBTTP (0.01 mmol) and H2BDC-Br (0.03 mmol) were ultrasonically dissolved in 1 mL of DMA, and Ni(NO3)2·6H2O (0.03 mmol) was dissolved in 0.1 mL of deionized water. After the two were mixed, 10 μL of tetrafluoroboric acid aqueous solution (52 wt%) was added and sealed in a pressure-resistant glass bottle. The porous coordination polymer crystals were obtained by thermal reaction at 90 °C for 48 hours.

[0038] Example 2

[0039] The organic ligands TMBTTP (0.02 mmol) and H2BDC-Br (0.06 mmol) were ultrasonically dissolved in 2 mL of DMA, and Ni(NO3)2·6H2O (0.08 mmol) was dissolved in 0.3 mL of deionized water. After the two were mixed, 30 μL of tetrafluoroboric acid aqueous solution (52 wt%) was added and sealed in a pressure-resistant glass bottle. The porous coordination polymer crystals were obtained by thermal reaction at 100 °C for 24 hours.

[0040] Example 3

[0041] The organic ligands TMBTTP (0.04 mmol) and H2BDC-Br (0.20 mmol) were ultrasonically dissolved in 5 mL of DMA, and Ni(NO3)2·6H2O (0.2 mmol) was dissolved in 1.5 mL of deionized water. After the two were mixed, 100 μL of tetrafluoroboric acid aqueous solution (52 wt%) was added and sealed in a pressure-resistant glass bottle. The porous coordination polymer crystals were obtained by thermal reaction at 100 °C for 24 hours.

[0042] Example 4

[0043] The organic ligands TMBTTP (0.1 mmol) and H2BDC-Br (0.4 mmol) were ultrasonically dissolved in 10 mL of DMA, and Ni(NO3)2·6H2O (0.5 mmol) was dissolved in 2 mL of deionized water. After the two were mixed, 200 μL of tetrafluoroboric acid aqueous solution (52 wt%) was added and sealed in a pressure-resistant glass bottle. The porous coordination polymer crystals were obtained by thermal reaction at 120 °C for 18 hours.

[0044] The test results of the products obtained in the above examples are the same. The porous coordination polymer crystal obtained in Example 1 was taken for crystal structure determination, as shown below:

[0045] (1) Crystal structure determination:

[0046] Single crystals of appropriate size were selected under a microscope, and data were collected on a Bruker SMART APEXII CCD diffractometer. Absorption correction was performed using the SADABS program. SHELXL-2014 was used to solve and refine the structural data for F2 using the direct method and full-matrix least squares method. The crystallographic program used the single-suite Olex2 integrated system. All non-hydrogen atoms were anisotropically refined. The positions and thermal parameters of hydrogen atoms were determined, and the structure was refined by geometric calculations. The contribution of disordered solvent molecules was processed using the SQUEEZE program implemented in PLATON. See the structure diagram. Figure 3-5 The crystallographic data are shown in Table 1.

[0047] Table 1 Crystallographic data of metal organic framework materials

[0048]

[0049] Figure 1 The crystal photos show that the PCP-Br crystal morphology is spindle-shaped, the degree of crystallization is good, and the crystal size is between 0.05-0.35 mm.

[0050] The method of the present invention is used to enlarge the synthesis of PCP-Br, and the obtained powder sample is as follows Figure 2 As shown, it is proved that PCP-Br can be synthesized on a larger scale with a mass of 0.25 g.

[0051] Figure 3 and Figure 4 Metal center structure Figure 3 The three-dimensional framework diagram shows that in the three-dimensional framework structure of PCP-Br, its crystallographic asymmetric structural unit contains 1 Ni(II) ion, 1 / 3 -OH group, 1 H2BDC-Br ligand and 1 / 3 TMBTTP ligand;

[0052] The Ni(II) ion is coordinated with six atoms in an octahedral configuration, including four O atoms of carboxyl groups from different H2BDC-Br ligands, one O atom of the -OH group, and one N atom from the TMBTTP ligand;

[0053] Three adjacent Ni(II) ions are bridged by one -OH group and six carboxyl groups of six different H2BDC-Br ligands to form a typical trinuclear metal cluster [Ni3(μ3-OH)(COO)6];

[0054] Each metal cluster is alternately connected with H2BDC-Br ligands to form a three-dimensional porous structure with acs topological configuration; TMBTTP ligands connect [Ni3(μ3-OH)(COO)6] clusters, further dividing them into a three-dimensional framework with pacs topological structure.

[0055] Figure 5 The cage structure diagram shows that in the PCP-Br structure, there are cylindrical cage A and spindle cage B, wherein the upper and lower planes of the cylindrical cage A contain three [Ni3(μ3-OH)(COO)6] clusters and one TMBTTP ligand, respectively, and the wall of the cylinder is occupied by six H2BDC-Br, and the bottom diameter and height of the cylindrical cage A are 7.9 and 2.7 Å, respectively;

[0056] The upper and lower vertices of the spindle-shaped cage B are respectively occupied by one [Ni3(μ3-OH)(COO)6] cluster, and three [Ni3(μ3-OH)(COO)6] clusters are evenly distributed in the middle part. The vertices and the middle clusters are connected by H2BDC-Br ligands, and the three middle [Ni3(μ3-OH)(COO)6] clusters are connected by TMBTTP ligands. The distance between the vertices of the spindle-shaped cage is 8.2 Å, and the diameter at the middle position is 8.1 Å.

[0057] The powder samples obtained by the amplified synthesis were characterized by powder X-ray diffraction. Figure 6 The X-ray powder diffraction spectrum shows that the prepared PCP-Br porous coordination polymer powder is a pure phase, which is completely consistent with the diffraction peaks fitted with the single crystal structure. In addition, after the sample is immersed in an organic solution, subjected to a gas adsorption test, and treated with an aqueous solution of pH 4 to 10, its crystal structure remains unchanged, proving that the porous coordination polymer has a certain chemical stability.

[0058] Figure 7 The thermogravimetric curves show that the thermal stability of PCP-Br porous coordination polymer reaches 370 ℃.

[0059] Figure 8 The infrared spectrum of the porous coordination polymer further confirmed the coordination between the metal and the ligand in PCP-Br.

[0060] (2) Specific surface area characterization

[0061] Fig. 9 The PCP-Br porous coordination polymer material of the present invention is P / P N2 adsorption isotherms under the conditions of 0 = 1 and 77 K. It can be seen from the figure that the saturated N2 absorption of PCP-Br reaches 234.0 cm 3 / g −1 (STP). By fitting and analyzing the adsorption data, the specific surface area of ​​PCP-Br was obtained to be 822.7 m 2 / g −1 , the pore size distribution is 6.2-6.8 Å.

[0062] (3) Characterization of adsorption and separation performance:

[0063] Fig.10 The PCP-Br of the present invention is 298 K and 313 K and P / P The single component adsorption isotherms of CH4, CO2, C2H6 and C3H8 when 0 is 1.0. It can be seen from the figure that under the conditions of 298 K and 1 bar, the saturation absorption of the porous coordination polymer crystal material PCP-Br for CH4, CO2, C2H6 and C3H8 is 15.93 cm 3 / g, 53.14 cm 3 / g, 64.61 cm 3 / g, 75.76 cm 3 / g, and the maximum absorption capacity for CH4, CO2, C2H6 and C3H8 is 11.47 cm at 313 K and 1 bar. 3 / g, 37.02 cm 3 / g, 47.64 cm 3 / g, 66.23 cm 3 / g. It can be seen that PCP-Br has significant differences in the adsorption performance of CH4, CO2, C2H6 and C3H8, indicating that it has the potential to separate CH4 / CO2 / C2H6 / C3H8 mixed gases.

[0064] Fig.11 The adsorption heat curve of PCP-Br for CH4 and other components (CO2, C2H6, C3H8) of the present invention is shown in Figure 2. In the porous coordination polymer PCP-Br material, the near-zero adsorption Q of CH4, CO2, C2H6 and C3H8 is stThe values ​​are 18.9 kJ / mol, 24.8 kJ / mol, 32.1 kJ / mol and 44.5 kJ / mol respectively. The calculation results show that the PCP-Br material has different adsorption forces on the four gas molecules, and the order of adsorption strength is C3H8>C2H6>CO2>CH4.

[0065] Fig.12 The figure is a schematic diagram of the equimolar dynamic breakthrough curve of PCP-Br of the present invention for CH4 and other components (CO2, C2H6, C3H8) under 298 K. The adsorption-breakthrough test of the four-component natural gas mixture was carried out using a multi-component adsorption breakthrough curve analyzer. 1.2 g of the activated sample was filled in a penetration column (inner diameter 6 mm) to form a fixed bed. The gas flow rate was adjusted so that the volume percentage concentration ratio of CH4 / CO2 / C2H6 / C3H8 in the four-component mixed natural gas was 1:1:1:1, and it was passed through the filled bed. The total flow rate of the mixed gas through the adsorption column was 2 mL / min, and the test temperature was 298 K. By continuously passing the mixture through the PCP-Br bed and monitoring the change of CH4 / CO2 / C2H6 / C3H8 concentration at the outlet of the adsorption bed with time in real time, the breakthrough curve of CH4 / CO2 / C2H6 / C3H8 was drawn. As can be seen from the figure, CH4 first penetrates the PCP-Br bed, followed by CO2, C2H6 and C3H8 after a certain interval. The penetration time difference between CO2, C2H6 and C3H8 and CH4 in the porous coordination polymer crystal material bed is 18.2, 35.9 and 58.1 min / g, respectively. The results show that PCP-Br can achieve the separation of CH4 / CO2 / C2H6 / C3H8 natural gas mixtures and has the potential to become a natural gas purification and separation material.

[0066] Fig.13 The cyclic penetration curve of the PCP-Br test of the present invention for adsorption separation of CH4 / CO2 / C2H6 / C3H8 mixed natural gas. After the adsorption separation process of CH4 / CO2 / C2H6 / C3H8 mixed natural gas, the sample can be regenerated by purging in a He atmosphere at a flow rate of 30 mL / min at 100 °C. As can be seen from the figure, there is no obvious change in performance after three cycles. It proves that PCP-Br has the potential to be an efficient and renewable gas separation material in industrial adsorption separation of CH4 / CO2 / C2H6 / C3H8 mixed natural gas.

Claims

1. A bromine-functionalized porous coordination polymer, characterized in that: The chemical formula of the bromine-functionalized porous coordination polymer is [Ni3(OH)(TMBTTP)(BDC-Br)3], wherein one of the ligands used is 4,4',4'-(2,4,6-trimethylbenzene-1,3,5-triphenyl)tripyridine TMBTTP, and the second ligand is H2BDC-Br which is 2-bromoterephthalic acid, named PCP-Br; The crystal structure of PCP-Br belongs to the trigonal system, and the space group is P- 31c, the unit cell parameters are: a = 16.943(3)Å, b =16.943(3)Å, c=15.034(6)Å, α = β = 90 o , γ = 120 o ; In the three-dimensional framework structure of PCP-Br, its crystallographic asymmetric structural unit includes 1 Ni(II) ion, 1 / 3 -OH group, 1 H2BDC-Br ligand and 1 / 3 TMBTTP ligand; The Ni(II) ion is coordinated with six atoms in an octahedral configuration, including four O atoms of carboxyl groups from different H2BDC-Br ligands, one O atom of the -OH group, and one N atom from the TMBTTP ligand; Three adjacent Ni(II) ions are bridged by one -OH group and six carboxyl groups of six different H2BDC-Br ligands to form a typical trinuclear metal cluster [Ni3(μ3-OH)(COO)6]; Each metal cluster is alternately connected with H2BDC-Br ligands to form a three-dimensional porous structure with acs topology; TMBTTP ligands connect [Ni3(μ3-OH)(COO)6] clusters, further dividing them into a three-dimensional framework with pacs topology; In the PCP-Br structure, there are cylindrical cages A and spindle-shaped cages B, wherein the upper and lower planes of the cylindrical cage A contain three [Ni3(μ3-OH)(COO)6] clusters and one TMBTTP ligand, respectively, and the wall of the cylinder is occupied by six H2BDC-Br. The bottom diameter and height of the cylindrical cage A are 7.9 and 2.7 Å, respectively. The upper and lower vertices of the spindle-shaped cage B are respectively occupied by one [Ni3(μ3-OH)(COO)6] cluster, and three [Ni3(μ3-OH)(COO)6] clusters are evenly distributed in the middle part. The vertices and the middle clusters are connected by H2BDC-Br ligands, and the three middle [Ni3(μ3-OH)(COO)6] clusters are connected by TMBTTP ligands. The distance between the vertices of the spindle-shaped cage is 8.2 Å, and the diameter at the middle position is 8.1 Å.

2. A method for preparing the bromine-functionalized porous coordination polymer as claimed in claim 1, comprising the following steps: Under sealed conditions, organic ligand 4,4',4'-(2,4,6-trimethylbenzene-1,3,5-triphenyl)tripyridine, 2-bromoterephthalic acid and nickel nitrate hexahydrate were dissolved in N , N - A mixed solution of dimethylacetamide and water, and an appropriate amount of acid is added to adjust the acidity of the solution, the acid is a 52wt% tetrafluoroboric acid aqueous solution, a sample is obtained through a solvent thermal reaction, and then the sample is activated to obtain a PCP-Br porous coordination polymer crystal material.

3. The method for preparing a bromine-functionalized porous coordination polymer according to claim 2, characterized in that: The temperature of the solvent thermal reaction is 90-120° C., and the reaction time is 18-48 hours.

4. The method for preparing a bromine-functionalized porous coordination polymer according to claim 2, characterized in that: The molar ratio of the organic ligand TMBTTP, H2BDC-Br and Ni(NO3)2·6H2O is 1:(3~5):(3~5); Each 0.1 mmol of TMBTTP corresponds to 10-12.5 mL of N , N - dimethylacetamide; N , N -The volume ratio of dimethylacetamide and water is 1:(0.1~0.4); Per 1 mL N , N -Dimethylacetamide corresponds to 10~30 μL of 52 wt% tetrafluoroboric acid aqueous solution.

5. The method for preparing a bromine-functionalized porous coordination polymer according to claim 2, characterized in that: The sample activation method comprises the following steps: firstly, washing the synthesized sample three times with ethanol, immersing the washed sample in an ethanol solution for 48 hours, stirring continuously and replacing the ethanol six times, filtering, and then drying in a vacuum oven at 100° C. for 5 hours to obtain an activated sample.

6. Use of the bromine-functionalized porous coordination polymer as claimed in claim 1 in the purification of natural gas.

Citation Information

Patent Citations

  • Coordination polymer material with multistage pore passage structure and preparation method thereof

    CN102161671A

  • Synthesis method of terephthalic acid containing cadmium coordination polymer

    CN105884804A